Chance and Intent : Managing the Risks of Innovation and Entrepreneurship. - Bodde, David L. (Taylor & Francis, 2012)
A compact and readable book will help executives, entrepreneurs, and venture investors learn to search out and plan for those enterprise hazards that reside outside the bell curve, the conventional domain of risk: Uncertainty, where outcomes can be characterized in advance, reliable estimates cannot be made for the likelihood that they will occur; Ambiguity, where the events and outcomes cannot be well characterized, in some cases because we cannot imagine them and in others because characterization depends upon the institutional interests or cultural values of the observer; and, Ignorance, wh.